Re-Examining The Financial Literacy – SME Growth Nexus: Fresh Evidence from Causal Mediation Analysis - Addo, Selma Dzifa; Asante, Joseph; Mensah, Emmanuel (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
The importance of SMEs to the growth of emerging economies cannot be overemphasized. SMEs remain an important source of employment and economic growth for most developing economies. However, it has been found that, most SMEs in developing countries are unable to survive even up to their fifth year of operation due to a multiplicity of factors including the level of financial literacy and risk attitude of SME owners. The current study aims to examine the effect of financial literacy on SME growth mediated by the risk attitude of SME owners. The study’s data was collected from SME owners/managers in Ghana. 500 questionnaires were administered and out of the 432 retrieved, 400 were deemed useful for analysis using causal mediation. The study found a significantly positive association between financial literacy and SME growth in the main outcome model. Also, risk attitude was found to be positively related to financial literacy in the mediation model, whereas risk attitude further mediated the relationship between financial literacy and SME growth which demonstrates that risk attitude plays an intermediary role in the association between financial literacy and SME growth. Our results support the dual process theory of reasoning, according to which decisions made by entrepreneurs to improve the growth and sustainability of their businesses are influenced by two different systems of thought: the automatic unconscious system, which is based on their risk tolerance, and the intentional conscious system, which weighs numerous factors and models in light of their financial literacy.